РАЗРАБОТКА И ЭКСПЕРИМЕНТАЛЬНОЕ ИССЛЕДОВАНИЕ ИНФОРМАЦИОННОЙ ТЕХНОЛОГИИ ПОКОМПЛЕКТНОГО ПЛАНИРОВАНИЯ ПОЗАКАЗНОГО ДИСКРЕТНОГО ПРОИЗВОДСТВА - Поносов, Иван Николаевич; Кучуганов, Валерий Никонорович; Касимов, Денис Рашидович (Интеллектуальные системы в производстве, 2015)
In the paper we propose a new informational technology of the operational production planning, which includes calculating the duration of manufacturing parts, creating aggregated groups of parts (groupkits) and scheduling. The Managed Problem Solver is used for obtaining the optimized kit-based plans of product manufacturing. Planning at the level of groupkits is characterized by a smaller number of variants to be considered. At that the effectiveness, in general case, is decreased as the count of groups grows, but the system’s flexibility is improved, which is important with a large range of components, plans become easy to read and edit.